OPTIma: a tracking solution for proton computed tomography in high proton flux environments. (1st April 2023) - Winter, A.; Aitkenhead, A.; Allinson, N.; Allport, P.; Esposito, M.; Green, S.; Kirkby, K.J.; MacKay, R.I.; Manger, S.; Merchant, M.J.; Price, T.; Pyatt, S.; et al.
Abstract: Currently there is a large discrepancy between the currents that are used for treatments in proton beam therapy facilities and the ultra low beam currents required for many proton CT imaging systems. Here we provide details of the OPTIma silicon strip based tracking system, which has been designed for performing proton CT imaging in conditions closer to the high proton flux environments of modern spot scanning treatment facilities. Details on the physical design, sensor testing, modelling, and track reconstruction are provided along with Monte-Carlo simulation studies of the expected performance for proton beam currents of up to 50 pA at the nozzle when using a σ = ∼10 mm spot scanning cyclotron system. Using a detailed simulation of the proposed OPTIma system, a discrepancy of less than 1% on the Relative Stopping Power is found for various tissues when embedded within a 150 mm diameter Perspex sphere. It is found that by accepting up to 7 protons per bunch it is possible to operate at cyclotron beam currents up to 5 times higher than would be possible with a single proton based readout, significantly reducing the total beam time required to produce an image, while also reducing the discrepancy between the beam currents required for treatment and those used for proton CT.